Information security : threat from employees - Erceg, Aleksandar (Array, 2019)
Information security inside the organization is becoming a major issue in the modern and global world. Information accessibility and security are a major issue where user behaviour plays an important role. Information security user behaviour is becoming an increasing threat to their organization information security. Since the organization is investing in and implementing information security systems, the issue of employees’ behaviour has become increasingly important. This paper aims to show how workers treat information security and is looking upon so called “people problem”. In the research, the personal behaviour of health care professionals and workers in a Croatian production company in relation to information security was tested. Results have shown that the overall behaviour of respondents in production company is more responsible and security awareness with proper use of passwords is associated with knowledge about the importance of security application in their work. Further research is recommended.